No-reference image quality assessment algorithm for contrast-distorted images enhanced by using directional contrast feature in curvelet domain - Ahmed I.T.; Der C.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Image enhancement; Image retrieval; Signal processing; Curvelets; Directional contrasts; Distorted images; No-reference image quality assessments; Support vector regressor; Image quality